Wheeze in infancy: protection associated with yeasts in house dust contrasts with increased risk associated with yeasts in indoor air and other fungal taxa. Issue 11 (10th October 2013) - Behbod, B.; Sordillo, J. E.; Hoffman, E. B.; Datta, S.; Muilenberg, M. L.; Scott, J. A.; Chew, G. L.; Platts‐Mills, T. A. E.; Schwartz, J.; Burge, H.; Gold, D. R.
Abstract: Background: While fungal exposures are assumed to provoke wheeze through irritant or allergenic mechanisms, little is known about the differential effects of indoor and outdoor fungi on early‐life wheeze. Methods: In a Boston prospective birth cohort of 499 at‐risk infants, culturable fungi in bedroom air and dust and outdoor air were measured at the age of 2–3 months. Wheeze was determined using bimonthly telephone questionnaires. Odds ratios were estimated for an interquartile increase in fungal natural log‐transformed concentrations, adjusting for predictors of wheeze and potential confounders. Results: Increased odds of 'any wheeze' (≥1 vs 0 episodes) by age one were positively associated with indoor dust Alternaria [odds ratio (OR) = 1.83; 95% confidence interval (CI), 1.07–3.14], Penicillium [OR = 1.18; (0.98–1.43)], and Cladosporium [OR = 1.47; (1.16–1.85)]; indoor air Penicillium [OR = 1.26; (0.92–1.74)]; and outdoor air Cladosporium [OR = 1.68; (1.04–2.72)]. In contrast, indoor dust yeasts were protective [OR = 0.78; (0.66–0.93)]. 'Frequent wheeze' (≥2 vs <2 episodes) by age one was borderline associated with dust yeasts [OR = 0.86; (0.70–1.04)] and indoor air yeasts [OR = 1.53; (0.93–2.53)]. Alternaria concentration was associated with any wheeze for children with maternal mold sensitization [OR = 9.16; (1.37–61.22)], but not for those without maternal mold sensitization [OR = 1.32; (0.79–2.20)]. Conclusions: While wheeze rates were higher with exposures to fungal taxa considered to be irritant or allergenic in sensitive subjects, yeasts in the home had a strong protective association with wheeze in infancy. Molecular microbiologic studies may elucidate specific components of innate microbiologic stimulants that lead to contrasting effects on wheeze development.